THE CREATIVITY OF ISLAMIC EDUCATION TEACHERS IN UTILIZING DIGITAL LEARNING MEDIA AT MTS MUHAMMADIYAH LAKITAN - Yulianda, Erlina; Guslianto, Guslianto; Ernayenti, Ernayenti (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The development of digital technology has significantly transformed educational practices, including Islamic Religious Education (PAI). This change requires teachers to adapt and demonstrate creativity in utilizing digital media to meet students’ needs and characteristics. This study aims to describe the creativity of PAI teachers in using digital learning media at MTs Muhammadiyah Lakitan and to identify supporting and inhibiting factors. The research employs a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing. The findings show that teachers have utilized laptops, projectors, presentations, instructional videos, and simple interactive media. Supporting factors include professional commitment, basic technological skills, minimal facilities, and institutional support, while inhibiting factors include limited infrastructure, unstable internet access, time constraints, and lack of training.